2018
DOI: 10.3390/min8040144
|View full text |Cite
|
Sign up to set email alerts
|

The Merensky Cyclic Unit, Bushveld Complex, South Africa: Reality or Myth?

Abstract: The Merensky Unit, Bushveld Complex, is commonly described using genetic terms such as "cyclic unit", typically without careful consideration of the connotations. We suggest that this contributes to the debate on processes forming the unit. This study integrates an extensive field study with detailed petrographic and textural analyses of the Merensky Unit to determine whether it is a "cyclic unit" sensu stricto. The study indicates that the bulk of the platinum-bearing chromitite-feldspathic orthopyroxenite de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…Grobler et al ( 2019 ) recognized four major units below the MZ that are correlative of UCZ units in the eastern and western BIC: Bastard Cyclic Unit (BCU), Merensky Cyclic Unit (MCU), Footwall Cyclic Unit (FCU), and UG-2 Cyclic Unit (UG2CU). We are adopting this nomenclature but without the “cyclic” qualifier for simplicity and to avoid the genetic connotations of the term as discussed in Irvine ( 1982 ) and Hunt et al ( 2018 ). Figure 1 shows representative examples of some of the main lithologies, obtained from the drill core used in this study (UMT094).…”
Section: Geological Backgroundmentioning
confidence: 99%
“…Grobler et al ( 2019 ) recognized four major units below the MZ that are correlative of UCZ units in the eastern and western BIC: Bastard Cyclic Unit (BCU), Merensky Cyclic Unit (MCU), Footwall Cyclic Unit (FCU), and UG-2 Cyclic Unit (UG2CU). We are adopting this nomenclature but without the “cyclic” qualifier for simplicity and to avoid the genetic connotations of the term as discussed in Irvine ( 1982 ) and Hunt et al ( 2018 ). Figure 1 shows representative examples of some of the main lithologies, obtained from the drill core used in this study (UMT094).…”
Section: Geological Backgroundmentioning
confidence: 99%
“…To explain the formation of the coarse-grained feldspathic orthopyroxenite enriched in PGE, and associated chromitite in the Merensky Reef, several authors have invoked the reaction between a late-stage hydrous melt with an unconsolidated cumulate assemblage [23][24][25][26][27]. On the basis of natural observations supported by experimental results, formation of tiny Os-Ir-Ru PGM inclusions in chromitite can be modeled by a sequence of crystallization events controlled by sulfur fugacity The textural position and the coarse grain size of laurite crystals, as well as their paragenesis including hydrous silicates, suggest crystallization at a late stage from a volatile-rich melt enriched in As and Cl, after coalescence of an immiscible sulfide liquid.…”
Section: Origin Of the Zoned Laurite In The Merensky Reefmentioning
confidence: 99%
“…Several theories for the origin of the Merensky Reef have been proposed, and they have been recently summarized by [25]. The proposed genetic models include: (i) gravitational settling of crystals that precipitated in the magma chamber during the orthomagmatic stage; (ii) hydrodynamic sorting of a mobilized cumulate slurry in a large magma chamber, under slow cooling; (iii) crystallization at the crystal mush-magma interface caused by a replenishment event; (iv) interaction of a hydrous melt with a partially molten cumulate assemblage; (v) intrusion of magmas as sills into undifferentiated norite; and (vi) intrusion of magma into a pre-existing cumulate pile ( [25] and references therein).…”
Section: Origin Of the Zoned Laurite In The Merensky Reefmentioning
confidence: 99%
“…As alternatives to models where the modally variable suite is an internally differentiated entity, as described above, or where the anorthositic strata are induced by the intrusion of hot overlying magmas, Hunt et al (2018) have suggested that the apparent cyclicity of the Merensky Reef specifically is an artifact of the introduction of at least five separate magma influxes, based primarily on existing geochemical indicators, supported by crystal size distribution analysis.…”
Section: Transported Metals and Slurriesmentioning
confidence: 99%